Perencanaan Gedung Panti Asuhan Kana’an Jaya - Helen Gianditha Wayangkau; Alfian Adie Chandra; Agung Saputra; Enjelo Sio’ (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2022)
Kana'an Jaya Orphanage is one of the privately owned social institutions that was originally a shelter for abandoned children, and orphans who came from several areas of political conflict in Pegungan Papua. This orphanage is located in Kertosari Village, Jalan Sabronsari, West Sentani District. For this reason, the Civil Engineering Department Community Service team took the initiative to plan the development of buildings and spaces for children's activities such as eating, studying, resting, etc. as well as a Budget Plan (RAB) needed for construction. Activities carried out for 6 months include the structural design process. This activity resulted in a design document consisting of structural calculations, two-story building drawings and proposals for funding assistance.